Thermal properties and residual strength after high temperature exposure of cement mortar using ferronickel slag aggregate - Saha, Ashish; Sarker, Prabir; Golovanevskiy, Vladimir (Elsevier BV, 2019)
This study evaluates the thermal properties of cement mortar using by-product ferronickel slag (FNS) fine aggregate and its residual strength after high temperature exposure. Compressive strength of mortar increased when FNS was used up to 50% replacement of sand and then reduced with further increase of FNS. Volume of permeable voids (VPV) increased by 4% and 7% respectively for using 50% and 100% FNS fine aggregate. Thermal conductivity of mortar decreased from 2.34 W/m.K for using 100% sand to 1.65 W/m.K and 1.16 W/m.K for 50% and 100% FNS, respectively. Similarly, specific heat increased from 2.18 MJ/m3.K to 2.43 MJ/m3.K for 100% replacement of sand by FNS. These changes of VPV and thermal properties are attributed to the cavity of FNS particles, and their larger size and angular shape. Residual strengths of mortar after exposure to 800 °C were found marginally less for using FNS aggregate. This is attributed to the decrease of thermal conductivity of mortar by FNS. Overall, FNS aggregate showed improved thermal insulating properties and thermal mass of mortar without compromising compressive strength. Therefore, FNS can be considered for use as an energy efficient sustainable building material.